HPLC-UV를 이용한 수질 중의 항생제류 동시분석 - 조성희; 정병화; 이원용; 정봉철; 이정애 (한국환경분석학회, 2006)
In the last decades, antibiotics have been widely used against diseases for human and animal as well as industrial farming. After a fraction of the drugs are metabolized to inactive compounds, but a significant amount is excreted as active metabolites. Accumulation of antibiotics in lakes and streams has raised concern regarding the toxicity to aquatic organisms and the emergence of strains of antibiotics resistant bacteria. We developed an analytical method for antibiotics in water based with solid-phase extraction (SPE) in high performance liquid chromatography (HPLC) coupled to ultraviolet detection (UV). We sample loading and elution tested various pH conditions to get maximum recovery in solid phase extraction. Under pH 4 condition (adjusted with 1 N HCl), water samples of 1 L was loaded onto Sep-Pak C18 cartridge. Antibiotics were separated within 25 min using C18 column (4.5 mm × 150 mm, 5 μm) and a mobile phase consisted of water (pH 2.5 adjusted with formic acid) and acetonitrile using a gradient program at a flow rate of 0.5 ml/min. The analysis of antibiotics separated was performed using UV detector with wavelengths of 265 and 285 nm. The calibration range was 0.01~5 ng/ml and the linearity of the method was over 0.992. The detection limits, defined as a 3 times of maximum S/N ratio, were lain in the range of 10-50 pg/mL. The recovery was over 90%. This method considered very sensitive with a pg/mL low detection limit level compare to its simple extraction step. We suggest that this method would be useful to evaluate the antibiotics concentration in environmental water.